Respuesta :

14.  (2x - 1)(x + 7) = 0

Using the zero factor property, we know that either the first or second terms (or both) must be equal to 0 if their product is 0.  We can set each term equal to 0 to find the solutions:

2x - 1 = 0
2x = 1
x = 1/2

x + 7 = 0
x = -7

15.  [tex] x^{2} +3x=10[/tex]

To solve this equation, you first need to set it equal to 0:

[tex]x^{2} +3x=10 \\ x^{2} +3x-10 = 0[/tex]

Next, it can be factored:

[tex]x^{2} +3x-10 = 0 \\ (x+5)(x-2)=0[/tex]

Finally, we can solve just like we did above:

x + 5 = 0
x = -5

x - 2 = 0
x = 2

16.  [tex]4x^2=100[/tex]

First, you can simplify by dividing each side by 4:

[tex]4x^2=100 \\ x^2=25[/tex]

Now, set the equation equal to 0:

[tex]x^2=25 \\ x^2-25=0[/tex]

Next, factor:

[tex]x^2-25=0 \\ (x+5)(x-5)=0[/tex]

Finally, find the solutions:

x + 5 = 0
x = -5

x - 5 = 0
x = 5
ACCESS MORE